Servicescape and Satisfaction as Antecedent of Revisiting Intention to Tourist Destination of Lake Toba - Sulistya Rini, Endang; F. Sembiring, Beby Karina (Opción, 2019)
One of the main tourist destinations in Indonesia is Lake Toba. It is located in the province of North Sumatra and is the biggest volcanic lake in the Southeast Asia region. The lake has a stunning view and several attractions that tourists can explore, from cultural experience, as well as natural and man-made at- tractions. Unfortunately, upon closer inspection, the lake is being polluted by household products as well as industrial waste, which resulted in the change of the lake’s water quality and odor. The method that was used for the research was qualitative mixed with quantitative with descriptive technique. The data acquisition was done by asking 160 tourists who have visited the lake before. The result found some empirical evidence that show a positive correlation be- tween ambient conditions and artifact with the interest to revisit Toba Lake. Meanwhile , the spatial layout and functionality variable do not directly or indirectly have a positive impact on revisiting the lake. The findings of this study could inform the local government to make some efforts to increase the number of tourists visiting the lake.